The Effect of the Addition of Guava Leaf Extract (Psidium guajava L.) to Coconut Milk Yoghurt (Niyoghurt) as A Functional Food - Sinaga, Hotnida; Suryanto, Dwi; Dary, Raihan (Postgraduate, University of Mataram, 2023)
Niyoghurt is yoghurt made from coconut milk. Coconut milk has a creamier, softer texture, and provides a distinctive taste compared to cow’s milk. Guava leaf contain a flavonoid compound, quercetin, which is antibacterial. This study aimed to evaluate the effect of the addition of guava leaf extract (Psidium guajava L.) to coconut milk yoghurt (niyoghurt) as a functional food. This study aimed to identify the water content, ash content, fat content, protein content, pH, total lactic acid, antioxidant activities, and hedonic color, flavor, taste, and texture from two types guava leaves (guava leaf and crystal guava leaf) and different concentration of extract (3%, 4%, and 5%). The results of the study showed that types of guava leaves had very significantly effects (P<0.01) on protein content, total lactic acid, hedonic color, texture and taste. The concentration of guava leaf extract had a very significantly effect (P<0.01) on fat content, protein content, total lactic acid, antioxidants, hedonic color, aroma, texture and taste, but did not have a significantly effect (P>0.05) on water content and ash content. The interaction between the type and concentration of guava leaf extract had a very significantly effect (P<0.01) on the hedonic color, texture, aroma and taste.